2021
DOI: 10.1051/0004-6361/202140319
|View full text |Cite
|
Sign up to set email alerts
|

Revealing asymmetrical dust distribution in the inner regions of HD 141569

Abstract: Context. The combination of high-contrast imaging with spectroscopy and polarimetry offers a pathway to studying the grain distribution and properties of debris disks in exquisite detail. Here, we focus on the case of a gas-rich debris disk around HD 141569A, which features a multiple-ring morphology first identified with SPHERE in the near-infrared. Aims. We obtained polarimetric differential imaging with SPHERE in the H-band to compare the scattering properties of the innermost ring at 44 au with former obse… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 80 publications
4
14
0
Order By: Relevance
“…In HD 141569, we detect more disk emission in the west side of the ring R3 than the ADI detection in Singh et al (2021). We also detect a large fraction of the full ring including the backside for AK Sco, while the previously published ADI result (Janson et al 2016) was only able to see the forward-scattered side.…”
Section: Robust Recovery Of Disk Features With Rdimentioning
confidence: 43%
“…In HD 141569, we detect more disk emission in the west side of the ring R3 than the ADI detection in Singh et al (2021). We also detect a large fraction of the full ring including the backside for AK Sco, while the previously published ADI result (Janson et al 2016) was only able to see the forward-scattered side.…”
Section: Robust Recovery Of Disk Features With Rdimentioning
confidence: 43%
“…One plausible explanation is that such multiple-ring geometries are generated by instabilities rather than shaped by planets, for instance based on the so-called "photo electric" effect [107], which implies that the gas compound is not negligible in these system with gas to dust ratio close to unity. CO gas was detected at least in HIP 73145 and HD 141569, with the latter being categorized as a gas-rich debris disk and showing a very strong match between the gas and dust distribution [108,109]. To explain this it has been shown that collisions within planetesimals in a belt can release both second generation dust and gas explaining their colocation [110].…”
Section: Morphology and Interaction With Planetsmentioning
confidence: 99%
“…Finally, in all NIRCam and MIRI images of HD 141569A, we will scrutinize the disk morphology to look for direct and indirect evidence of planets. The system shows large cavities that suggest dynamical clearing by planets (e.g., Wyatt 2005;Konishi et al 2016;Perrot et al 2016), and asymmetries in the dust density distribution possibly caused by a massive collision between planetesimals (Singh et al 2021). The longer wavelengths of JWST offer a more favorable contrast regime to probe for the presence of giant planets than existing shorter wavelength observations, as discussed in §1.2.…”
Section: Coronagraphy Of a Young Circumstellar Diskmentioning
confidence: 99%